Sosialisasi Gerakan Masyarakat Cermat Cerdas Menggunakan Obat (Gema Cermat) Di Kabupaten Seluma - Oktavia, Desi; Theresiana , Yunita; Novira , Deasy; Nurdan , Jon Hendri; Pansori , Hartian; Maju , Firman Bintara (Jurnal Kewirausahaan dan Bisnis, 2024)
One of the efforts to develop health in every health care facility is to achieve patient safety standards by utilizing of rational drugs. Constraints faced to achieve safe and quality health services due to lack of information on the use of drugs provided by health workers either the lack of compliance with the use of prescribed drugs, or the many people who use drugs without a prescription / self-medication (self medication). The aim of community service is expected to provide education to the public about the use of rational medicine as well as the socialization of the government program of the Smart Community Using Drugs in Ilir Talo Health Center, Seluma Regency. The devotion method by providing counseling as well as a quiz competition about the counseling material to find out the extent of understanding about the information presented. The results of this devotion are improving the understanding of the community, especially at the level of the Ilir Talo Health Center, Seluma Regency, so that correct use of drugs or for storing medicines. The implementation of counseling as one of the community service programs has been carried out well and received a good response and was very enthusiastic about participating in counseling by the participants by asking questions about rational use of medicines and how to store and dispose of medicines properly and correctly.